Reporting on Qualitative Components of A Research Project - Lyn English (Universitas Sebelas Maret, 2021)
In this brief commentary, I first overview the strengths and weaknesses of qualitative research in education and also briefly consider mixed methods. I then offer a few suggestions for reporting on particular methodological components and the results of qualitative research. I do not address the reporting on other significant components such as the literature review and theoretical framework, given that these aspects are generic to both qualitative and quantitative research. The points I make are brief and are by no means exhaustive. Nevertheless, it is hoped that they offer some guidance for authors in education who adopt primarily qualitative methods.